Safeguarding The Use Of Electricity In Mines - H. H. Clark (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1914)
ELECTRICITY must be safeguarded everywhere that it is used. The conditions that exist underground make the use of safeguards more essential there than almost anywhere else. Electric Shock Electric shock is the greatest danger in connection with the use of electricity in mines, because conditions existing underground are so favorable to its occurrence. Men are often obliged to work in more or less uncertain light near bare wires that are carrying dangerous potentials. The fact that the men are standing on the earth practically connects them to one terminal of the electric generator. The most dangerous piece of electrical equipment underground is the trolley wire. It is necessarily bare and extends for long distances throughout a mine, often less than a man's height from the track rail. Sometimes the making up of trips of cars must be done near low-hanging trolley wires. All bare wires offer the same danger that trolley wires do, although not to the same extent. Apparatus that has accidentally come in contact with the ungrounded side of an electric circuit is almost as dangerous as the trolley wire. A severe and even fatal shock may be obtained by coming in contact with the frame of a motor or a switch box that has become charged with electricity, or "alive," as it is usually termed. It is also possible to obtain shocks from the frames of locomotives and cars if track. sanding, poor bonding or a similar cause has put a high resistance to earth in the path of the current.